Given that [tex]K(x)= 2x^2 -5x +3[/tex] as a function, the value of K(-3) can be found by substituting x for -3 into the function which will give us: [tex]\mathbf{K(-3) = 36}[/tex]
Given the function, [tex]K(x)= 2x^2 -5x +3[/tex], to find the value of K(-3), substitute -3 for x into [tex]K(x)= 2x^2 -5x +3[/tex].
[tex]K(-3)= 2(-3)^2 -5(-3) +3\\\\K(-3) = 18 + 15 + 3\\\\\mathbf{K(-3) = 36}[/tex]
Therefore, given that [tex]K(x)= 2x^2 -5x +3[/tex] as a function, the value of K(-3) can be found by substituting x for -3 into the function which will give us: [tex]\mathbf{K(-3) = 36}[/tex]
Learn more here:
https://brainly.com/question/19027807